Relation between Caste and Vocational Aspiration of the Students: Exploring the Influence of Caste on Students' Vocational Aspirations in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The caste of the student has a strong influence on our vocational aspiration too. India is a country of diverse group of people, community, cultures, languages and Institutions. Our social system is quite different and probably unique from the rest of the world. Our eighty percent population reside in villages which is poor and under privileged. Even in the cities, the people are generally traditional like rural people because of their cultural background. The recent census report revealed that in our country, education is still less in comparison to western and advanced countries. In addition to all these, majority of Indian population have same family occupations. They are generally traditional and superstitious. In such a condition, the educational and vocational goals of most of the students are not based on primary and realistic considerations like students of advanced countries. Thus, the results based on the studies made on students of an advanced country cannot be realistic for our students. In advanced countries career plans are made on primary considerations like ability, aptitude, interest, intelligence, achievements etc. But in our country, due to lack of opportunity and several other reasons, they are based on secondary considerations like parents’ advice, employment opportunity, Social of family occupations etc. In another words, we can say frankly that here the career plans, education vocational goals, success in education and vocation are based on extraneous grounds and are accidental in grounds are accidental in nature. Here one is doctor or a College Teacher, or Police Officer or Military personnel by accident in most of the cases Thus it is desirable to make studies on educational and vocational aspirations of students in Indian context very few studies have come to light in Indian context (eg Joshi, 1963 Kanungo, 1960 Reddy, 1978 Saboo, 1979 Singh and Prasad, 1969Suman, 1985) etc. These studies cannot be judged as enough So more through and well-planned studies on this aspect are needed. This will help us to a great extent, in understanding our students in better way in present context. The impact of caste effects the level of vocational aspiration the level of the students.